(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article analyzes the legacy of Abu Ali Ibn Sina (Avicenna) and demonstrates in which areas the modern medical science and education of Uzbekistan continue to draw from his works. The article discusses the methodological principles of the Canon of Medicine, specific examples of their application in curricula, scientific research on pharmacology and herbal medicine, institutional memory, and international cooperation. The article provides recommendations for further integration of the historical heritage into the healthcare system.